Model Pembelajaran Religious Culture Sebagai Basis Pengembangan Kurikulum Pendidikan Islam - Lutfi Rachman (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2022)
Abstract : Humans are social beings who need each other to form social groups in their daily life. Religion is a value system adopted by the community that can shape the style and dynamics of social life, because religion is a source of inspiration, driving force and also acts as a controller for the continuity and tranquility of human life in a social group or society. In carrying out their duties and functions as social beings, the religious values ​​adopted are needed. The implementation of character education needs to be developed in an approach of habituation or cultivation through religious culture which is essentially closely related to character education, namely trying to produce students who are moral or well behaved. So the focus in this problem is education. Because education is one way out to foster the character of the younger generation in a directed, programmed, and maximal way in order to form a young generation that is intellectually intelligent and has moral quality.